Effective Application of Plasma Lighting Facility Based on Electrodeless Sulfur Lamp for Electrical Regeneration - Frolova, T. I. (45th IEEE International Conference on Plasma Science (ICOPS 2018), 2018)
Today, due to the intensive depletion of fossil resources on Earth, there is a need to use renewable energy sources. The most interesting is the photoelectric conversion of solar energy into electrical energy. Although the Sun is the largest source of energy on Earth and supplies 99.98% of the total energy of our planet, however, the intensity and spectral distribution of its radiation depends on geographical location, climatic, weather, and seasonal conditions, etc. Therefore, in the process of our life, artificial light sources are often used. Modern light sources must satisfy a number of parameters, combining high luminous efficiency and efficiency of generated radiation (a wide range of spectral distribution and color rendering), durability and environmental friendliness with low cost and variety of applications fields.